Characterization Of Lithium Vanadium Oxide Anode With Agar Binder In Aqueous Rechargeable Lithium Ion Batteries - Soo, Kuan Lim (Universiti Sains Malaysia, 2017)
The purpose of this work is to study the effect of agar binder in lithium vanadium oxide (LiV3O8) anode on the structural, morphology and electrochemical performance of the electrode. The anode electrode is fabricated by adding the active material (LiV3O8), electrical conductor (graphene) and binder (agar) in a specified ratio with percentage of agar binder being varied. The working electrode is compacted and allowed to be characterized as a half-cell setting. The structural analysis indicate that the agar binder has successfully banded the phases of LiV3O8 and graphene together prior to cycling. The morphological analysis proven that the agar binder is able to prevent delamination of the active mass. The electrochemical performances further consolidate the findings where the characterization is done in 5 M LiNO3 electrolyte. From cyclic voltammetry findings, with an optimized scan rate of 0.1 Mv s-1, the best performing electrode is one with 8 wt% agar binder. The anode half-cell also had high reversibility and high coefficient diffusion of lithium ions at 1.315 x 10-6 and 3.046 x 10-6 cm2 s-1 for anodic and cathodic peaks respectively. LiV3O8 anode demonstrated initial specific discharge capacity of 48 mAh g-1 under optimized scan rate 0.1 mV s-1. A good cyclic performance with 45 mAh g-1 (capacity retention of 93.75%) at the 10th cycle. The capacity fading upon cycling was supported by increasing charge transfer resistance from the impedance analysis. However, cracks observed on the surface of LiV3O8 anode upon cycling in morphological analysis indicated anisotropic volume change in the lattice parameter c upon intercalation/de-intercalation of lithium ions.